Health professionals’ routine practice documentation and its associated factors in a resource-limited setting: a cross-sectional study - Demsash, Addisalem Workie; Kassie, Sisay Yitayih; Dubale, Abiy Tasew; Chereka, Alex Ayenew; Ngusie, Habtamu Setegn; Hunde, Mekonnen Kenate; Emanu, Milkias Dugassa; Shibabaw, Adamu Ambachew; Walle, Agmasie Damtew (BMJ health & care informatics, 2023)
ObjectivesDocumenting routine practice is significant for better diagnosis, treatment, continuity of care and medicolegal issues. However, health professionals’ routine practice documentation is poorly practised. Therefore, this study aimed to assess health professionals’ routine practice documentation and associated factors in a resource-limited setting.MethodsAn institution-based cross-sectional study design was used from 24 March up to 19 April 2022. Stratified random sampling and a pretested self-administered questionnaire were used among 423 samples. Epi Info V.7.1 and STATA V.15 software were used for data entry and analysis, respectively. Descriptive statistics and a logistic regression model were employed to describe the study subjects and to measure the strength of association between dependent and independent variables, respectively. A variable with a p value of <0.2 in bivariate logistic regression was considered for multivariable logistic regression. In multivariable logistic regression, ORs with 95% CIs and a p value of <0.05 were considered to determine the strength of association between dependent and independent variables.ResultsHealth professionals’ documentation practice was 51.1% (95% CI: 48.64 to 53.1). Lack of motivation (adjusted OR (AOR): 0.41, 95% CI: 0.22 to 0.76), good knowledge (AOR: 1.35, 95% CI: 0.72 to 2.97), taking training (AOR: 4.18, 95% CI: 2.99 to 8.28), using electronic systems (AOR: 2.19, 95% CI: 1.36 to 3.28), availability of standard documentation tools (AOR: 2.45, 95% CI: 1.35 to 4.43) were statistically associated factors.ConclusionsHealth professionals’ documentation practice is good. Lack of motivation, good knowledge, taking training, using electronic systems and the availability of documentation tools were significant factors. Stakeholders should provide additional training, and encourage professionals to use an electronic system for documentation practices.